2010
DOI: 10.1007/s00508-009-1275-7
|View full text |Cite
|
Sign up to set email alerts
|

Tako-Tsubo syndrome: an important differential diagnosis in patients with acute chest pain

Abstract: Patients with TTC display clinical symptoms and electrocardiographic findings that mimic acute myocardial infarction. A history of a preceding stressful event in elderly women, typical echocardiographic findings of TTC, and only a mild elevation of cardiac markers will be informative. Acute-coronary angiography should be performed in order to rule out acute coronary occlusion and to avoid inadequate treatment such as thrombolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Across many different series, approximately 2% of all patients presenting to the hospitals with suspected acute coronary syndrome are usually identified with takotsubo syndrome 6,11,12 , with the postmenopausal female predominance described above [13][14][15][16] . If only female cases with suspected acute coronary syndrome are considered, up to 10% patients are ultimately diagnosed with takotsubo syndrome 10 .…”
Section: Epidemiologymentioning
confidence: 99%
“…Across many different series, approximately 2% of all patients presenting to the hospitals with suspected acute coronary syndrome are usually identified with takotsubo syndrome 6,11,12 , with the postmenopausal female predominance described above [13][14][15][16] . If only female cases with suspected acute coronary syndrome are considered, up to 10% patients are ultimately diagnosed with takotsubo syndrome 10 .…”
Section: Epidemiologymentioning
confidence: 99%
“…Studies have shown that SCM was associated with chronic psychological or neurological diseases [14,15]. Our results implied that the influence of the chronic circulatory diseases on SCM may be underestimated.…”
Section: Scm Profile In Patients With Chronic Diseasesmentioning
confidence: 66%
“…Summers MR et al [14] reported that psychiatric illness had a high prevalence antecedes the onset of SCM. Primetshofer D et al [15] found that SCM patients frequently suffered from neurological disease. Whether SCM is likely to prevalence in individuals with high level of catecholamines, such as chronic circulatory diseases patients, is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…It Son's departure for holidays [15] Hospital discharge [16] Official letter [17] Dinner invitation [17] has been known for many years that the psychological stress of a burglary can precipitate a major health crisis in elderly patients, necessitating urgent admission to a hospital [2]. TTC, induced by emotional or physical stress, has been a well-acknowledged acute cardiac problem with considerable morbidity and mortality due to arrhythmia, cardiogenic shock, and ventricular rupture [1,3].…”
Section: Discussionmentioning
confidence: 99%